Biological Monitoring Among Workers Exposed to Inorganic Lead and Its Compounds - Saso Stoleski; Elisaveta Stikova; Jovanka Karadzinska-Bislimovska; Dragan Mijakoski (ID Design Press, 2011)
Objective: To explore the association between lead biomarkers and their deviations in the circumstances of occupational exposure, and influence of life style factors. Material and Methods: We performed cross-sectional study using 60 workers occupationally exposed to lead compared with 60 controls. All examinees were assessed by Questionnaire, and laboratory testing concerning blood lead level (BLL), activity of delta-aminolevulinic acid dehydratase (ALAD) in blood, concentration of delta-aminolevulinic acid (ALA) and coproporphyrin in urine, reticulocytes and erythrocytes with basophilic stippling (EBS). Results: The mean values of BLL and ALA were significantly higher, and mean ALAD activity was significantly lower in lead workers than in controls. Lead workers also had a higher rate of abnormal BLL, ALAD, and ALA, significant for BLL and ALAD. The average BLL values among exposed workers and controls in men were significantly higher. There was strong inverse correlation between distribution of ALAD values in exposed workers due to their BLL values. Significant correlation with mean ALAD values was shown for alcohol consumption, form of compounds, and use of protecting equipment, whereas with mean BLL values was shown for age, gender, exposure duration, smoking, and alcohol consumption. Conclusion: The data confirmed the association between occupational exposure and lead biomarkers abnormalities.
Keywords: Blood lead level; aminolevulinic acid dehydratase; aminolevulinic acid; biological markers; Occupational exposure; toxicity